간척지의 환경변화가 흰뺨검둥오리 서식에 미치는 영향 - 진선덕(Seon-Deok Jin); 백인환(In Hwan Paik); 박치영(Chi Young Park); 최성훈(Seong Hoon Choi); 유재평(Jae Pyeong Yu); 백운기(Woon Kee Paek); 강태한(Tehan Kang) (한국조류학회지, 2018)
시화호 환경변화에 따른 흰뺨검둥오리의 개체수 변화를 확인하기 위해 2008년 1월부터 2014년 12월까지 매월 1회씩 조사하였다. 흰뺨검둥오리의 평균 개체수는 12,204개체이었고 점차적으로 감소하는 경향을 보였다. 변동지수(Fi)는 2010년에 2.16로 가장 높았다. 개체군 변화경향은 겨울철은 급격한 감소, 가을철과 봄철에는 보통감소, 여름철은 보통 증가경향을 보였다. 주요 서식지로는 북측간척지, 방수제, 탄도수로, 인공습지 이었다. 기온과의 상관관계는 봄, 여름, 가을은 음의 상관관계를 보였고, 겨울은 양의 상관관계를 보였다. 간척지 환경변화에 따라 흰뺨검둥오리의 군집에 영향을 미치고 있어 본 연구와 같은 자료를 토대로 효과적인 관리방안이 필요하다. In order to investigate the changes in the population of Spot-billed ducks due to changes in reclaimed land, we conducted a monthly survey from January 2008 to December 2014 at the Shihwa Lake. The average number of Spot-billed ducks was 12,204 individuals. The average population was decreased. The yearly index of fluctuation (Fi) was the highest at 2.16 in 2010. TRIM(TRends and Indices for Monitoring data) showed a steep decline in winter and a moderate decrease tendency in autumn and spring. However, in the summer season, it showed an moderate increasing tendency. The main habitat were Northland reclaimed land, agricultural land and wetland area, Tando waterway, Shihwa artificial wetland in upstream. The correlation between the number of Spot-billed ducks and the temperature was negatively correlated in spring, summer, autumn. However, winter was showed positive correlation. Therefore, it affects the community of Spot-billed ducks due to environmental changes of reclaimed land. In future, effective management is needed to prepare alternative habitat based on basic data like this study for the conservation and management of Spot-billed ducks during reclamation construction. KCI Citation Count: 0